Stability Analysis of the Dinar Dirham as an Alternative Currency for the Islamic World - Sri Sudiarti; Wahyu Syarvina (International Journal of Economics (IJEC), 2022)
The dinar and dirham can last decades to become a formidable medium of exchange, as gold and silver have the highest suitability as money rather than commodities. However, some people believe there are alternative currencies besides gold and silver. Starting to implement and use the dinar and dirham currencies is part of muamalah activities. The wheel of Islamic economics is driven by the dinar and dirham cycle, where a currency is used as a medium of exchange, storage, or fair value of wealth. This will lead to the prosperity of humanity. This study aims to find out evidence of the stability of the dinar and dirham values by using qualitative research methods which are methods of understanding and extracting meaning from what happens to various individuals or groups, originating from humanitarian or social problems. Sources of data obtained from textbooks, journals, manuscripts, etc., and sources obtained from trusted websites. The dinar and dirham currencies are alternatives that can be used as a medium of exchange in the current economy so that the period of socialization and education for the community must be in collaboration with other factors in various elements of society, the world of education, and most importantly the policies made by the government are in line with in tune with the principles of Islamic economics in various aspects of life.